Metaphorization of Tactile Gestures in Russian - Yurina, Elena; Shlotgauer, Elena (Vestnik Volgogradskogo gosudarstvennogo universiteta. Serii͡a︡ 2, I͡A︡zykoznanie., 2024)
The article discusses the study of processes involved in the formation and representation of ideas about tactile gestures in language. These gestures, being a part of a person’s physical experience, convey communication-relevant information, and are known as physical communication signals. The article examines models for figurative interpretations of situations involving physical interaction, which are expressed in a language through verbs with the semantic meaning of physical impact, as well as various linguistic units that reflect the results of physical perception. The study considers the cases of metaphorical usage of verbs denoting physical contact (trogat’ (touch), gladit’ (stroke), teret’ (rub), shlepat’ (slap), etc.), verbs derived from them, words of other parts of speech (schekotlivyi (ticklish), tsarapina (a scratch)), as well as the semantics of the phraseological expressions that include the above mentioned units (gladit’ po sherstke (stroke the fur), trogat’ za dushu (touch the soul) etc.). The material is organized according to the lexico-phraseological field of “Tactility”, which is divided into subfields based on the type of physical contact: touch, movement on a surface, forceful action, irritating effect, and compressive effect. Within each subfield, the elements are connected through derivational and motivational relationships. As a result, specific spheres of metaphorical mapping, such as “Human”, “Society”, and “Material world”, are identified and described. It has been determined that the cognitive foundation for metaphorical mappings is based on the nature of physical interactions (compression, sliding, pressure, irritation, etc.). The evaluative component of physical metaphors stems from associations with pleasant or unpleasant physical and emotional experiences that arise during or as a result of the interaction between subjects.